Effect of Fortification of Massage Oil for Breastfeeding Mothers on Physical, Chemical and Organoleptic Tests of Jitu Oil - Ningsih, Dewi Andariya; Andini, Dwi Margareta; Atiqa, Sri Nur; Fadhilah, Syifa; Kholifah, Umi Nur (Journal of Global Research in Public Health, 2023)
This massage oil is called Jitu Oil, which means complementary therapy massage oil. The addition of oil is expected to help facilitate the massage process and provide relaxation for nursing mothers, and can produce hormones that play a major role in the process of lactation and breastfeeding to the fullest. The oil used virgin coconut oil with the addition of lavender and lime to add relaxation during the massage process. This research is an experimental research with 5 treatments. The location of the research was carried out in the Working Area of the Arjasa Health Center. The time of the research was conducted from February to March 2023. The population in this study were breastfeeding mothers. The sample in this study consisted of 31 respondentused simple random sampling technique. The clarity test was found to be clear without impurities, the chemical test showed the substances contained in the oil and the organoleptic test p-value = 0.000 <0.05, it can be concluded that there is a difference between the composition and the organoleptic quality parameters of color. If seen from the Mean Rank value, it shows that F5 is higher than the others. p-value = 0.000 <0.05, it can be concluded that there is a difference between the composition of the organoleptic aroma quality parameters. If seen from the Mean Rank value, it shows that F4 is higher than the others. So that Jitu Oil can be widely used and produced to complement massage for nursing mothers.